Late Complication Associated With the Treatment of Orbital Floor Fracture With Titanium Mesh. Issue 6 (September 2018) - Costa, Pedro Jorge Cavalcante; de Gauw, Johnny Holanda; Costa Filho, José Zenou; Moreira, Raphael Teixeira; Ribeiro Júnior, Paulo Domingos
Abstract : Abstract: Treatment of orbital fractures involves restoration of lost bone anatomy and orbital volume. Among the materials used for this purpose, the titanium mesh is widely used due to its effectiveness and low complication rate related to distortion especially in non-traumatic events. This study shows an atypical and late complication involving the deformation of the titanium mesh used during reconstruction of the orbital floor in a patient with orbital zygomatic complex fracture 5 months after the procedure and without traumatic etiology.